PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 9 DURI BARAT KECAMATAN MANDAU TAHUN AJARAN 2015/2016 - Deswita '; Hendri Marhadi; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of student learning outcomes IPS, it can be seen from the results of social studies students of class III Elementary School 9 Duri Barat, with the average value of the class 65.47. This study aims to improve learning outcomes IPS third grade students of SD Negeri 9 Duri Barat. Application of Cooperative Learning Model Type Student Teams Achievement Division. The study design is a PTK with 2 cycles. Based on the analysis of research data after applying cooperative learning model Student Team Achievement Division (STAD) the percentage of the first cycle of activity of the first teachers to meet an increase of 62.5% 70.83% at the second meeting. The percentage of activity the teachers first meeting of the second cycle increased 79.16% and the second meeting of the second cycle into 91.66%. The percentage of student activity first meeting of the first cycle of the second meeting increased 58.33% to 70.83%, 79.16% also increased that the first meeting of the second cycle, increased to 87.5% in the second meeting of the second cycle. The results of student learning basic score with the average value of 65.47 in the first cycle increased the average value of 69.0 grade with the percentage increase in the percentage of 5.11% of learning outcomes of students who completed 66.66%, and the second cycle increased with grade - an average of 75 by the percentage increase in the percentage of 12.70% of learning outcomes of students who completed 83.33%. The results showed that the implementation of cooperative learning model Student Team Achievement Division, can improve learning outcomes IPS third grade students of SD Negeri 9 Duri Barat Key Words: Student Teams Achievement Division, learning outcomes IPS